A long waiting time from diagnosis to treatment decreases the survival of non-small cell lung cancer patients with stage IA1: A retrospective study - Liu, Bin; Qian, Jia-Yi; Wu, Lei-Lei; Zeng, Jun-Quan; Xu, Shu-Quan; Yuan, Jin-Hua; Zheng, Yong-Liang; Xie, Dong; Chen, Xiaolu; Yu, Hai-Hong (Frontiers in Surgery, 2022)
Objective: The prognostic effect of delayed treatment on stage IA1 non-small cell lung cancer (NSCLC) patients is still unclear. This study aimed to explore the association between the waiting time before treatment and the prognosis in stage IA1 NSCLC patients. Methods: Eligible patients diagnosed with pathological stage IA1 NSCLC were included in this study. The clinical endpoints were overall survival (OS) and cancer-specific survival (CSS). The Kaplan-Meier method, the Log-rank test, univariable, and multivariable Cox regression analyses were used in this study. Propensity score matching was used to reduce the bias of data distribution. Results: There were eligible 957 patients in the study. The length of waiting time before treatment stratified the survival in patients (<3 months vs. ≥3-months, unadjusted hazard ratio [HR]=0.481, P=0.007; <2 months vs. ≥2-months, unadjusted HR=0.564, P=0.006; <1 month vs. ≥1-month, unadjusted HR=0.537, P=0.001). The 5-year CSS rates were 95.0% and 77.0% in patients of waiting time within 3 months and over 3 months, respectively. After adjusting for other confounders, the waiting time was identified as an independent prognostic factor. Conclusions: A long waiting time before treatment may decrease the survival of stage IA1 NSCLC patients. We propose that the waiting time for those patients preferably is less than one month and should not exceed two months.